2006
DOI: 10.1128/iai.00111-06
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Esters of Enterococcal Lipoteichoic Acid Play a Role in Biofilm Formation and Resistance to Antimicrobial Peptides

Abstract: Enterococcus faecalis is among the predominant causes of nosocomial infections. Surface molecules like D-alanine lipoteichoic acid (LTA) perform several functions in gram-positive bacteria, such as maintenance of cationic homeostasis and modulation of autolytic activities. The aim of the present study was to evaluate the effect of D-alanine esters of teichoic acids on biofilm production and adhesion, autolysis, antimicrobial peptide sensitivity, and opsonic killing. A deletion mutant of the dltA gene was creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
181
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(188 citation statements)
references
References 47 publications
4
181
1
2
Order By: Relevance
“…The n-butanol method and HIC on octyl-sepharose were used to extract and purify LTA. The butanol method can be used to extract structurally intact LTA and has been widely used to extract LTA from numerous types of Gram-positive bacteria, such as Staphylococcus aureus, Streptococcus pneumoniae, E. faecalis and Streptococcus gordonii (6,19,23,24). Furthermore, SDS-PAGE and Coomassie Blue G-250 staining were used to detect protein contamination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The n-butanol method and HIC on octyl-sepharose were used to extract and purify LTA. The butanol method can be used to extract structurally intact LTA and has been widely used to extract LTA from numerous types of Gram-positive bacteria, such as Staphylococcus aureus, Streptococcus pneumoniae, E. faecalis and Streptococcus gordonii (6,19,23,24). Furthermore, SDS-PAGE and Coomassie Blue G-250 staining were used to detect protein contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, LTA is the key virulence factor due to its major role in pathogenicity. It has been demonstrated that E. faecalis LTA can stimulate leukocytes to release certain mediators associated with inflammatory response (5) and plays a critical role in biofilm formation (6). E. faecalis LTA is also known to inhibit the repair mechanism of periapical bone by decreasing the proliferation of human osteoblast-like cells and inducing apoptosis (7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dltD gene encodes a membraneassociated protein, which facilitates the binding of Dcp and Dcl for ligation of Dcp with D-alanine. Disruption of any one of the dlt genes will eliminate D-alanylation of LTA.D-Alanylation confers a positive charge upon LTA and has been demonstrated to have a role in the regulation of autolytic activity (Fischer et al, 1981), the binding of Mg 2+ (Archibald et al, 1973), intragenic coaggregation (Clemans et al, 1999), biofilm formation (Fabretti et al, 2006;Gross et al, 2001), adherence to mammalian cells (Abachin et al, 2002;Weidenmaier et al, 2004) There is evidence that bacteria can modulate the level of D-alanyl esters on LTA. An increase in the level of D-alanyl ester on LTA has been reported under low external pH conditions (Ellwood & Tempest, 1972;MacArthur & Archibald, 1984), and a decrease in D-alanyl ester contents has been reported when metal cations, such as Mg 2+ , Ca 2+ , Na + and K + , are present in the culture medium (Fischer & Rösel, 1980;Heptinstall et al, 1970;Kiriukhin & Neuhaus, 2001;Koch et al, 1985; Koprivnjak et al, 2006;Reusch & Neuhaus, 1971).…”
mentioning
confidence: 99%